Precise Activation of Ammonia and Carbon Dioxide by an Iminodisilene. (15th July 2018) - Wendel, Daniel; Szilvási, Tibor; Henschel, Daniel; Altmann, Philipp J.; Jandl, Christian; Inoue, Shigeyoshi; Rieger, Bernhard
Abstract: The activation of NH3 and CO2 is still an ambitious target for multiply bonded sub‐valent silicon compounds. Now, the precise splitting of the N−H bond of ammonia by (Z)‐imino(silyl)disilene1 to give trans‐1, 2‐adduct2 a at low temperatures (−78 °C) is presented. According to DFT calculations, the stereospecific hydroamination follows a similar mechanism as the recently reported anti‐addition of H2 to the Si=Si bond of1 . The aminosilane2 b could also be obtained as the formal silylene addition product under thermodynamic reaction control. By applying low temperatures, the activation of CO2 with1 selectively afforded the cis‐oxadisilacyclobutanone7‐c as [2+2] cycloadduct. By performing the reaction directly at ambient temperatures, a mixture of three different‐sized silacycles (4 –6 ) was observed. Their formation was investigated theoretically and their structures were revealed with separate experiments using1 and the oxygenation agents N2 O and O2 .